PENGEMBANGAN INSTRUMEN TES KEMAMPUAN BERARGUMENTASI PADA MATERI IMPULS DAN MOMENTUM - Febi Dwi Putri (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTThe ability to argue is an ability that needs to be mastered by students to pass ontheir knowledge to others. This study aims to develop a test instrument for theability to argue on impulse and momentum material. The test instrument wasadapted from the Toulmin's Argument Pattern (TAP) model. This researchincludes research and development by taking a 3-D model that is define, design,and develop. A total of five items of description are made based on indicators ofargumentation ability. In the results of expert validation it is obtained that thetest instrument is feasible to be developed by considering the improvement of theitems by expert advice. The results of the development of the whole item is valid,and has a high reliable value of 0.78.Keywords: development of instruments, the ability to argue, impulses andmomentum.